Práticas de governança eletrônica: um estudo nos portais dos municípios mineiros - Silva, Patrícia Conceição da (2018)
The development of communication and information technologies, besides modifying the daily life of organizations and individuals, influences the way of relationship between society and government. It is in this context that electronic governance emerges, a concept and a practice that has risen in the public sector all over the world and that has contributed to the formation of new relations between citizens and the State from the electronic delivery of services, governmental organizations and forms of interaction with citizens. Given this, the research seeks to clarify: what are the indices of e-governance practices used by the municipalities of Minas Gerais (IGEM) and are they related to the municipal human development index (IDHM)? To elucidate the problem, a sample was collected with the municipalities of Minas Gerais State that have an HDIH equal to or higher than the national HDI, equal to or greater than 0.754. The present research is characterized as objectives as descriptive research, as to the nature as applied research, as for the bibliographic and documentary procedures, and finally about the approach of the qualitative-quantitative problem. To verify the compliance of the official websites of the municipalities with the e-governance practices, a checklist was made up of 65 questions, based on the methodology proposed by Mello (2009). Subsequently, the relationship between the results of the e-governance index and the municipalities' MDIs was established through the Pearson correlation, using the SPSS software, version 21. It was concluded that the websites of the cities surveyed have more characteristics of e-government and require greater attention from public managers so that they can develop e-governance that is capable of allowing new forms of interaction between government officials and citizens, especially as regards encouraging the effective participation of society in decisions of the government. participation is fundamental to good e-governance. In addition, it was verified that there is a positive correlation between the IGEM and IDHM variables of the municipalities of Minas Gerais that have HDI equal to or higher than the national HDI, classified as high HDI, and, therefore, a significant correlation with mean effect. However, although there is a positive correlation between the IGEM and the IDHM, the results found for the e-governance index allow us to infer that although it was expected that the high human development index presented by the municipalities would also reflect the adoption of e-governance practices in their websites, this was not the result found in the cities surveyed. Thus, the websites of the municipalities surveyed present a need for improvements in the adoption of e-governance practices and especially in maintaining and updating practices already implemented.